2007
DOI: 10.1017/s0021859607007241
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping with pulses to concentrate nitrogen and sulphur in wheat

Abstract: The effects of intercropping wheat with faba bean (Denmark, Germany, Italy and UK) and wheat with pea (France), in additive and replacement designs on grain nitrogen and sulphur concentrations were studied in field experiments in the 2002/03, 2003/04 and 2004/05 growing seasons. Intercropping wheat with grain legumes regularly increased the nitrogen concentration of the cereal grain, irrespective of design or location. Sulphur concentration of the cereal was also increased by intercropping, but less regularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 23 publications
5
39
1
4
Order By: Relevance
“…Yet, as we indicated above, intercrops would be a way of improving harvested grain quality and in particular its protein concentration compared with the traditional sole cropping (e.g. Jensen 1996a; Knudsen et al 2004;Gooding et al 2007;Bedoussac and Justes 2010a;Naudin et al 2010). Our results confirm that the protein concentration of the intercropped cereal is almost always greater than that of the respective cereal sole crop (Fig.…”
Section: Intercropping Improves the Protein Concentration Of The Ceresupporting
confidence: 84%
See 3 more Smart Citations
“…Yet, as we indicated above, intercrops would be a way of improving harvested grain quality and in particular its protein concentration compared with the traditional sole cropping (e.g. Jensen 1996a; Knudsen et al 2004;Gooding et al 2007;Bedoussac and Justes 2010a;Naudin et al 2010). Our results confirm that the protein concentration of the intercropped cereal is almost always greater than that of the respective cereal sole crop (Fig.…”
Section: Intercropping Improves the Protein Concentration Of The Ceresupporting
confidence: 84%
“…15). Gooding et al (2007) confirmed by Bedoussac andJustes (2010a, 2010b) explained that the intercropping effect on grain protein concentration of wheat was due to a higher soil N availability for the cereal on a per plant or a per grain basis in intercrop in comparison with sole crops. It was shown to be the result of: (i) the low competitiveness of legumes for mineral N compared with cereals, combined with (ii) competition for light, water and other nutrients, between the two species, which lead to limit intercropped cereal biomass and Fig. 14 Cereal partial land equivalent ratio for grain protein concentration as a function of cereal partial land equivalent ratio for grain yield (y=1.06x -0.16 ; R 2 =0.34***).…”
Section: The Lower the Soil Nitrogen Availability The Greater The Inmentioning
confidence: 91%
See 2 more Smart Citations
“…Pea was preferred to faba bean (Vicia faba L. sub. minor) because in previous studies in a similar environment in Southern Italy (Gooding et al 2007), a leafless pea cultivar performed better than faba bean in intercrop with the latter causing reduction in cereal yields. Sole crop (SC) treatments (WSC, BSC, OSC, TSC, PSC) were sown at the recommended seed density of 90 seeds m −2 for pea, 300 seeds m −2 for oat and barley and 400 seeds m −2 for wheat and triticale.…”
Section: Treatments and Experimental Designmentioning
confidence: 90%